2021
DOI: 10.3389/fpsyg.2021.699461
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Personality as a Predictor of Career Adaptability and Career Growth Potential: A View From Conservation of Resources Theory

Abstract: In the present study, we offered a new account for the development of career adaptability and the realization of career growth potential based on conservation of resources (COR) theory. Using data collected from 903 university students in China, we examined how and when proactive personality influences students’ career adaptability and career growth potential by introducing emotional exhaustion as a mediator as well as friend support and teacher individualized consideration as boundary conditions. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 65 publications
1
19
0
1
Order By: Relevance
“…Career construction requires career adaptability, meaning being ready to cope with uncertainties from unpredictable shifts in their job and working conditions ( Savickas, 1997 ). Many studies have argued the antecedents and consequences of career adaptability in predicting positive career-related outcomes ( Jiang, 2017 ; Zhuang et al, 2018 ; Gao et al, 2019 ; Ayala et al, 2020 ; Mei et al, 2021 ; Wang et al, 2021 ). As Obschonka et al (2018) have indicated career adaptability is important in responding to the uncertain environment in one’s occupational development.…”
Section: Career Construction Theorymentioning
confidence: 99%
“…Career construction requires career adaptability, meaning being ready to cope with uncertainties from unpredictable shifts in their job and working conditions ( Savickas, 1997 ). Many studies have argued the antecedents and consequences of career adaptability in predicting positive career-related outcomes ( Jiang, 2017 ; Zhuang et al, 2018 ; Gao et al, 2019 ; Ayala et al, 2020 ; Mei et al, 2021 ; Wang et al, 2021 ). As Obschonka et al (2018) have indicated career adaptability is important in responding to the uncertain environment in one’s occupational development.…”
Section: Career Construction Theorymentioning
confidence: 99%
“…Furthermore, when we consider career adaptability as a proactive behavior (Reference), the fact that career adaptability contains proactive components suggests that career adaptability and proactive personality may be related. Alike, Wang et al (2021) stated that proactive personality has a positive effect on career adaptability and however emotional exhaustion plays a mediating role in this effect. Specifically, proactive personality emphasizes the active side of individuals in life, and career adaptability is linked to the fact that individuals actively direct their careers even in changing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Braunstein-Bercovitz et al (2012) found that pessimism plays a mediating role in the relationship among anxious attachment and career indecision. Wang et al (2021) stressed proactive personality has a positive effect on career adaptability also emotional exhaustion plays a mediating role in this effect. Li (2019) investigated the relationship between proactive personality and career adaptability in a study of individuals studying at the university level.…”
Section: Career Pessimism As a Mediatormentioning
confidence: 95%
See 2 more Smart Citations